Comparative Efficacy of Chimeric Porcine Circovirus (PCV) Vaccines against Experimental Heterologous PCV2d Challenges - Wongchanapai, Pichanun; Yamsakul, Panuwat; Arunorat, Jirapat; Guntawang, Thunyamas; Sittisak, Tidaratt; Srivorakul, Saralee; Photichai, Kornravee; Thanawongnuwech, Roongroje; Sukmak, Manakorn; Pringproa, Kidsadagon (Veterinary sciences, 2023)
The objective of this study was to evaluate the efficacy of two multivalent commercial porcine circovirus (PCV) vaccines against heterologous PCV2d challenges. A total of 24 crossbred male pigs aged 26 days selected from a specific pathogen-free herd were randomly divided into four groups (six pigs per group) and assigned as follows: negative control (unvaccinated/sham-challenge), vaccinated with chimeric PCV1-2a vaccine (PCV1-2a/PCV2d-challenge), vaccinated with chimeric PCV1-2a-2b vaccine (PCV1-2a-2b/PCV2d-challenge) and positive control (unvaccinated/PCV2d-challenge). At 21 days after vaccination, the pigs were intranasally and intramuscularly inoculated with either sham or field isolates of PCV2d (PCV2d/149/TH/2020). After being challenged, blood samples were obtained weekly and analyzed for levels of PCV2d viremia, neutralizing antibodies, and IgG against PCV2. At 30 days post-challenge (DPC), the pigs were euthanized and then subjected to pathological evaluations and molecular analysis. The results indicated that pigs in the PCV1-2a-2b/PCV2d-challenge and the PCV1-2a/PCV2d-challenge groups possessed significantly greater levels of PCV2d-neutralizing antibody titer when compared with the positive control group. Moreover, pigs in the PCV1-2a-2b/PCV2d-challenge group exhibited a lower degree of severity in terms of gross lesion scores and lower levels of PCV2 viremia when compared with the positive control group. This study demonstrated that vaccinating pigs with either the PCV1-2a or PCV1-2a-2b chimeric vaccines elicits a potent immune response against PCV2d infection and reduces viremia after PCV2d inoculation in pigs.